Inventarisasi Kerentanan Longsor dengan Citra Landsat 8 OLI TIRS di Lereng Timur Gunung Agung - Jananuraga, Petrus Raki; Suyarto, R.; Kusmiyarti, Tati Budi (Fakultas Pertanian Universitas Udayana, 2024)
Landslide Vulnerability Inventory with Landsat 8 OLI TIRS Imagery on the Eastern Slope of Mount Agung. Landslides are one of the natural disasters that often occur in Indonesia and cause loss of life, property, and damage to facilities and infrastructure. Landslide vulnerability on the eastern slope of Mount Agung is categorized as medium to high, making the area very vulnerable to landslides, therefore an inventory of landslide vulnerability in the area is needed. This study aims to analyze the results of land cover interpretation using BSI vegetation index approach and supervised classification on the eastern slope of Mount Agung, Bali, compare the results of land cover accuracy test of BSI vegetation index approach interpretation and supervised classification, and analyze landslide vulnerability from 2013 to 2022. The method used in this research is qualitative by utilizing data taken from Landsat 8 OLI TIRS images recorded from 2013 to 2022 in the form of Blue band, Red band, Near Infrared band, and Shortwave Infrared 2 band. Land cover classification uses Bare Soil Index vegetation index analysis and supervised classification. The results showed that the comparison of the area of non-vegetated land distribution for each year of the Bare Soil Index analysis results was greater than the results of the analysis using supervised classification. The highest non-vegetated land area based on the results of the Bare Soil Index was in 2019 with an area of 11,469.60 ha, while the supervised classification occurred in 2017 with an area of 6,182.03 ha. The accuracy test results show that the BSI method is more accurate (82.86%) compared to the supervised classification method (62.86%). Non-vegetated land (vacant land) based on BSI that is included in the Movement Vulnerability Zone is an area vulnerable to landslides, its distribution changes due to various events that occur in the area such as forest fires, landslides, land use change, and others. The highest vulnerability area was in 2019 amounting to 1,779.03 ha while the lowest vulnerability area was in 2016 amounting to 1028.94 ha.